1987
DOI: 10.1111/j.1526-4610.1987.hed2704180.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Latent Dysnociception in Healthy Subjects

Abstract: SYNOPSIS Headache is the most common side effect of nitroglycerin, administered for angina pectoris. Two phases can be distinguished in nitroglycerin‐induced headache: the first phase (immediate headache), a mild sensation of temporal pulsating pain, can be due, at least in part, to the vasodilation provoked by nitroglycerin; the second phase (delayed headache), an increasing pain, possibly with nausea and vomiting, lasting even for a number of hours, is independent from the vasomotility, since it arises and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 14 publications
6
84
0
Order By: Relevance
“…1). This experiment confirmed previous observations by Sicuteri et al 31 that migraine sufferers have an immediate, as well as delayed headache, and that the latter, according to the patients, was indistinguishable from their spontaneous migraine attacks. The super sensitivity to GTN in migraine sufferers could be due either to the trait or state of migraine.…”
Section: Migrainesupporting
confidence: 82%
See 1 more Smart Citation
“…1). This experiment confirmed previous observations by Sicuteri et al 31 that migraine sufferers have an immediate, as well as delayed headache, and that the latter, according to the patients, was indistinguishable from their spontaneous migraine attacks. The super sensitivity to GTN in migraine sufferers could be due either to the trait or state of migraine.…”
Section: Migrainesupporting
confidence: 82%
“…In older literature, no distinction was made between the immediate headache after administration of GTN and the headache that occurred in migraine patients long after the administration of GTN. 1,30 Sicuteri et al 31 focused on this issue and suggested that migraine sufferers and first-degree relatives of migraine sufferers: 1) were more sensitive to GTN than normal controls; and 2) developed a delayed headache that was migraine-like. Because of a lack of explicit diagnostic criteria for migraine at the time, it was not possible to analyze whether the headache did or did not fulfill diagnostic criteria for migraine.…”
Section: Migrainementioning
confidence: 99%
“…[24][25][26][27][28][29] Several studies report that migraine patients are unusually sensitive to acute NTG-induced headache and delayed onset migraine attacks. 25,[30][31][32] Delayed NTG-induced headache also occurred in subjects without migraine, but with a positive family history. This occurred in 28.6% of patients with a positive family history and in no patients without a positive family history.…”
Section: Commentsmentioning
confidence: 99%
“…Nitroglycerin (NTG)-administration is a model of migraine, being able to generate migraine attacks in migraineurs (Sicuteri et al, 1987), and trigger activation and sensitization in the trigeminal system (Di Clemente et al, 2009). It is also well-known, that NTG-a nitric oxide donor (NO)-can initiate trigeminal activation and sensitization in animals as well (Pardutz et al, 2000;Tassorelli and Joseph, 1995).…”
Section: Introductionmentioning
confidence: 99%